PENGARUH PENGGORENGAN DAN CARA PENGERINGAN TERHADAP SIFAT ROTAN BALUKBUK (CALAMUS BURCKIANUS) DAN ROTAN SEUTI (CALAMUS ORNATUS) - Efrida Basri; Suparman Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This paper presents the result of laboratory drying tests on 1wo rattan species. The samples from each species were devided into two groups. The first group was fried in kerosene before drying, and the second was left unfried. Each group was then subjected to two drying conditions, namely drying under roof (in-door) and out-door. The test were terminated when the samples reached equilibrium moisture content, i.e . approximately 16%. The result of evaluation rattan qualitv based on colour is presented together with their drying speed. It shows that both balukbuk and seuti rattans when fried in kerosene dry faster than when untried. However, frying seems to produce darker colour after drving.